Polyunsaturated fatty acid in treatment resistant depression: A pilot study. (13th April 2021) - Jannini, T.; Longo, L.; Barone, Y.; Niolu, C.; Bernardini, S.; Siracusano, A.; Bertucci, P.; Lorenzo, G. Di
Abstract : Introduction: The deficiency of polyunsaturated fatty acids (PUFAs) and an alteration between the ratio of omega-6 and omega-3 PUFAs may contribute to the pathogenesis of depressive disorders. Objectives: To investigate the levels of omega-3 and omega-6 in red cell membranes (mPUFAs) and plasma (pPUFAs) of patients with treatment-resistant (TRD) and non-treatment resistant depression (non-TRD). Methods: TRD and non-TRD consisted of 75 patients enrolled at the Psychiatric and Clinic Psychology Unit of the University of Rome Tor Vergata, Rome, Italy, and met the DSM-IV criteria for major depressive disorder (MDD). A group of healthy controls (HC) matched for agender and age was enrolled. All blood samples were performed in conditions of an empty stomach between 07:00 am and 09:00 am. For each subject were obtained 5 ml of whole blood with the use of tubes for plasma with EDTA as an anticoagulant. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) for omega-3 and arachidonic acid (AA) for omega-6 were measured. Results: Levels of pPUFAs did not differ between the three groups. The mPUFAs were altered in the MDD. TRD and non-TRD had lower EPA and AA values respect to the HC. DHA in red cell membranes was lower in TRD than non-TRD and HC. Conclusions: Changes in levels of PUFAs in red cell membranes, but not in plasma, may be an important factor to evaluate the resistance to the pharmacological treatment.